Gestão das micros e pequenas empresas: um estudo no Município de Palmas - TO - Oliveira, Nilton Marques de (2021)
This study aims to analyze the management of micro and small companies in the city of Palmas - Tocantins State-TO - Brazil. The strategic planning of each company determines its objectives and desired goals and the way how the process will occur for such procurements. Literature review and field research were the adopted methodology. Twenty nine entrepreneurs from a universe of three hundred were selected compounding the sample for questionnaire application. The questionnaires took place from August to October, 2011. Issues related to aspects of management, planning, organization, leading, recruitment, selection, and training of staff, safety, instructions and orders, communication, motivation, control, information, and decision-making have been addressed. The main results suggest that entrepreneurs from Palmas-TO attach importance to planning, control and communication systems inside the company. Other highlighted aspects are the motivation and safety.